Highly stable and near-infrared responsive phase change materials for targeted enzyme delivery toward cancer therapy - Yuqiong Xia; Chang Liu; Xuejuan Zhao; Keyun Wu; Jianxia Cao; Yutian Cao; Cheng Zhu; Xianghan Zhang (Materials Today Bio)
Natural enzyme-based catalytic cascades have garnered increasing attention in cancer therapy, but their clinical utility is greatly limited due to loss of function during in vivo delivery. Here, we developed an enzyme delivering nanoplatform (GCI@RPCM) with great in vivo stability and achieve NIR-triggered enzyme dynamic therapy. This nanoplatform is created with encapsulation of nature enzymes (glucose oxidase and chloroperoxidase) and photothermal agent (indocyanine green) within tumor targeting and thermo-responsive phase change materials (RPCMs). With NIR irradiation for 10 min, GCI@RPCM can release 41 % of the enzymes and generate abundant reactive oxygen species (ROS), which showed significant tumor cell inhibition. After intravenous injection, GCI@RPCM can efficiently accumulate at the tumor site and local NIR treatment resulted in complete tumor eradication without detectable systemic toxicity. This study provides a highly stable and NIR-controllable smart delivery system and achieve enzyme dynamic therapy for enhanced breast cancer therapy.